(untitled) (American Journal of Research in Humanities and Social Sciences, 2026)
Early childhood caries (ECC) remains one of the most prevalent chronic diseases in pediatric populations worldwide and continues to pose a significant clinical and public health challenge. Although individual minimally invasive interventions have demonstrated effectiveness in controlling early carious lesions, limited evidence exists regarding the clinical impact of integrated, risk-based minimally invasive models that simultaneously address caries activity, lesion progression, and patient-related behavioral outcomes.